Bebras Informatics Contest: Criteria for Good Tasks Revised - Vaníček, Jiří (Informatics in Schools. Teaching and Learning Perspectives, 2014)
The Bebras International Contest on Informatics and Computer Fluency has significantly grown in the number of participating countries and participants in recent years. Six years ago Dagienė and Futschek determined the criteria for good contest tasks, which are frequently used by the International Bebras Committee for selecting and improving tasks for national contest organizers. New experience and findings from several surveys allow us to reconsider these criteria from a new viewpoint and to assess which of these criteria are still actual, which need revisions and whether some new criteria are needed if the process of creation of informatics tasks for the contest is to be improved. The paper discusses the issues of motivation, interactivity, multiple-choice answers and content topics. The reviewed criteria and categories might be useful for authors of Bebras tasks as well as for creators of informatics curricula.